Consensus statements on ablative radiotherapy for oligometastatic prostate cancer: A position paper of Italian Association of Radiotherapy and Clinical Oncology (AIRO). (June 2019) - D'Angelillo, Rolando M.; Francolini, Giulio; Ingrosso, Gianluca; Ravo, Vincenzo; Triggiani, Luca; Magli, Alessandro; Mazzeo, Ercole; Arcangeli, Stefano; Alongi, Filippo; Jereczek-Fossa, Barbara A.; Pergolizzi, Stefano; Pappagallo, Giovanni L.; et al.
Highlights: Ablative radiotherapy is an effective treatment for oligometastatic prostate cancer. The lack of randomized phase III trials hampers the generalization of this therapy. In clinical practice, ablative radiotherapy should be adopted in some cases only. This position paper explores available literature and proposes some recommendations. Abstract: Oligometastatic prostate cancer comprises a wide spectrum of conditions, ranging from de novo oligometastatic cancer at diagnosis to oligometastatic castration-resistant disease, which are distinct entities in terms of biology and prognosis. In order to clarify and standardize the clinical role of ablative radiotherapy in oligometastatic prostate cancer, the Italian Association of Radiotherapy and Clinical Oncology (AIRO) formed an expert panel to review the current literature and develop a formal consensus. Oligometastatic prostate cancer was defined as the presence of up to three metastatic lesions involving bones or nodes outside pelvis. Thereafter, four clinical scenarios were explored: metastatic castration-sensitive disease at diagnosis and after primary treatment, and metastatic castration-resistant disease at diagnosis and during treatment, where the role of ablative radiotherapy was defined either in conjunction with systemic therapy or as the only treatment in selected cases. This paper summarizes the current literature about these issues and the proposed recommendations.